Early Weaning in Endangered Delta Smelt: Effect of Weaning Time on Growth and Survival. (29th January 2022) - Hung, Tien‐Chieh; Ellison, Luke; Stevenson, Troy; Sandford, Marade; Schultz, Andrew A.; Eads, Angela R.
Abstract: Successful aquaculture operations strive to produce high‐quality, healthy fish while minimizing costs. One way to do this is to wean fish off live feed as soon as possible to a formulated dry feed. In this study, Delta Smelt Hypomesus transpacificus were weaned onto a dry feed diet at three life stages: early larval (14 days posthatch [dph]), late larval (60 dph), and juvenile (105 dph), and compared to a control group of fish receiving live prey to 160 dph according to current practices. Delta Smelt did not have high survival or growth when dry feed was introduced at 14 dph, and showed significant increases in growth but low survival when the weaning process was started at 60 dph. Fish going through the experimental weaning process starting at 105 dph showed higher growth and survival rates than the control regime, indicating that this is a more optimal time to wean them off the live prey diet. Our findings suggest that Delta Smelt production methods could be improved by weaning fish earlier than the 160 dph currently implemented at the conservation hatchery.